Catalytic co‐pyrolysis of packaging plastic and wood waste to achieve H2 rich syngas. (6th August 2020) - Bobek‐Nagy, Janka; Gao, Ningbo; Quan, Cui; Miskolczi, Norbert; Rippel‐Pethő, Dóra; Kovács, Kristóf
Summary: In this work, the co‐pyrolysis of pine sawdust and low‐density polyethylene (LDPE) was performed in a two‐stage fixed‐bed reactor to achieve hydrogen‐rich syngas and to investigate the effect of the parameters on gas yield and composition. Gas chromatography was used to confirm the content of the gas products. The pyrolysis was supported with Ni (in 5‐25 wt%) loaded on activated carbon (AC). The maximum hydrogen concentration was 392.8 mmol g −1 sample, which was achieved by the use of the 10% Ni‐AC catalyst. The influence of Ni loading on supporter was investigated by scanning electron microscope and transmission electron microscope techniques besides the thermogravity analysis. The increasing size of the Ni particles can be observed as a function of the Ni concentration on the catalyst. Carbon deposition was detected and the amorphous carbon seems more dominant than filamentous form. In addition, the effect of fluid residence time (water inlet and purge gas) on syngas yield was studied. Three different fluid residence times were investigated, and among them, the highest hydrogen yield was 392.8 mmol g −1 sample at 1.57 minutes residence time. Furthermore, the catalyst lifetime was studied using 10 wt% of Ni containing AC, and the average hydrogen concentration was 196.0 mmol g −1 sample over 15 cycles.